COUNTER-HEGEMONY IN LATIN AMERICA? UNDERSTANDING EMERGING MULTIPOLARITY THROUGH A GRAMSCIAN LENS - Burron, Neil (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional, 2014)
The rise of the “emerging economies” and the relative decline of US power hold forth the promise of a more multipolar and pluralistic world order. Perhaps nowhere is this as apparent as in the Americas, where left and centre-left governments have challenged the traditional imperialistic arrangements that have governed the region. What type of regional order will emerge in the Americas? How will this diverge from the current capitalist world order organized under the aegis of the Unites States? This article draws on classical Marxism and Gramscian thought to examine the interplay between hegemony and counter-hegemony in the Americas, focusing on Brazil, Bolivia, and Venezuela. By exploring the history and geopolitics of regional order, the emergence of the new left, and the ongoing dominance of the traditional oligarchy, it argues that counter-hegemonic change is still very much a work in progress.